2000
DOI: 10.1023/a:1008136520396
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Electron-electron repulsion energy () is presented as a new molecular descriptor to be employed in QSAR and QSPR studies. Here it is shown that this electronic energy parameter is connected to molecular quantum similarity measures (MQSM), and as a consequence can be considered as a complement to steric and electronic parameters in description of molecular properties and biological responses of organic compounds. The present strategy considers the molecule as a whole, thus there is no need to employ contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 16 publications
1
26
0
Order By: Relevance
“…In this sense, they developed the concept of E-states, an electrotopological-state index for atoms in a molecule. More recently, Carbo´-Dorca et al [29] proposed the use of electron-electron repulsion energy, in connection with molecular quantum similarity measures derived from quantum-chemical calculations, as a molecular descriptor in QSAR studies of biological activities [29].…”
Section: Charge Topological Indexes Approachmentioning
confidence: 99%
“…In this sense, they developed the concept of E-states, an electrotopological-state index for atoms in a molecule. More recently, Carbo´-Dorca et al [29] proposed the use of electron-electron repulsion energy, in connection with molecular quantum similarity measures derived from quantum-chemical calculations, as a molecular descriptor in QSAR studies of biological activities [29].…”
Section: Charge Topological Indexes Approachmentioning
confidence: 99%
“…Relatively little is known about the importance of this particular molecular descriptor in QSAR development, although it is certainly reasonable that the C À N bond is involved for this data set. Recently, Gironé s et al [65] have shown that the electron-electron repulsion energy of an entire molecule can be connected to so-called molecular quantum similarity measures and these authors found quite acceptable correlations of this descriptor with several biological activities. The a-polarizability also appears in several of our BMLR equations.…”
Section: Best Multiple Linear Regression (Bmlr) Approachmentioning
confidence: 99%
“…Within the ASA approach 1–7, electronic densities are expressed as a linear combination of spherical 1 s functions: where the coefficients { w i } are restricted to be positive definite in order to assure the physical meaning of the fitted density. A simple but very interesting particular case of the previous development consists in using a promolecular approximation.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…With the parameterized atomic densities \documentclass{article}\pagestyle{empty}\begin{document}$\rho_{a}^{\mathrm{ASA}}(\mathbf{r})$\end{document}, and the nuclear coordinates of any molecular system, PASA density is easily generated by using Eq. (3), producing a reasonable approximation to the molecular density, avoiding the ab initio theoretical calculation of electron density, and permitting the quantum similarity study of large molecular systems such as enzymes 3.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation